Conversor CC-CC híbrido de alto ganho com capacitor comutado para aplicações em conversões fotovoltaicas - Rodrigues, Brenna Theodora Machado Matos (2023)
This work presents the study and development of a high-gain hybrid DC-DC converter with switched capacitor for photovoltaic solar energy applications. The qualitative and quantitative analyzes of the converter are presented. The proposed converter is based on the boost converter integrated in the switched capacitor cells with the addition of a small resonant inductor. The mathematical modeling of the converter was developed to determine the resonance inductance value, where the converter was analyzed for inductance values from 1.5Uh to 2Uh, as well as the dimensioning of the components. This work presents simulation results and experimental results in which a 200 W prototype was assembled and the results are presented. In this way, this proposal presented some advantages: such as extended static gain, reduction of voltage stress in semiconductors and reduction of current peaks in switches, it also presented a maximum efficiency of 97.1% and a voltage gain equal to 10 was obtained.